Изучение влияния N-алканолов и хлорпромазина на гипотонический гемолиз эритроцитов барана и курицы в средах различного состава. - Ніпот, О.Є. (Вісник проблем біології і медицини – 2011. – Вип. 4 (90) – С. 56-60, 2011)
The article is dedicated the study of influence of n-alkanols (hexanol, butanol) and chlorpromazine on a level and speed of hypotonic hemolysis of red blood cells of hen and ram in medium, containing electrolyte (NaÑl, Na2SO4) and neelektrolit (sucrose). It is assumed that distinctions in protecting efficiency of the substanses in electrolyte and unelectrolyte medium, it is caused probably by the change of transport processes and permeability of membrane, and also electrostatic properties of its surface. The features of hypotonic hemolysis of red blood cells of different kinds (ram, hen) are discussed.-------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------Стаття присвячена вивченню впливу н-алканолів (гексанол, бутанол) і хлорпромазину. на рівень і швидкість гіпотонічного гемолізу еритроцитів курки та барана в середовищі, що містить електроліт (NaÑl, Na2SO4) і неелектроліт (сахароза). Передбачається наявність відмінностей у захисній ефективності речовин в електролітному та неелектролітному середовищі це зумовлено, ймовірно, зміною транспортних процесів і проникності мембрани, а також електростатичних властивостей її поверхні. Особливості гіпотонічного гемолізу червоної крові обговорюються клітини різних видів (баран, курка).
Study Of Influence N-Alkanols And Chlorpromazine On Hypotonic Hemolysis Of Red Blood Cells Of Ram And Hen In Medium Of Different Composition
Ніпот О.Є. Изучение влияния N-алканолов и хлорпромазина на гипотонический гемолиз эритроцитов барана и курицы в средах различного состава.Вісник проблем біології і медицини. 2011; 4 (90): 56-60
Keywords: гипотонический стресс; эритроциты барана; эритроциты курицы; n-алканолы